(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the issue of poetic speech in Uzbek linguistics, individual style in speech and its study. Also, comments on the scope of research on this topic, the term idiostyle, and the role of works devoted to the study of poetic text in linguopoetics are presented.